H-NS Nucleoid Protein Controls Virulence Features of Klebsiella pneumoniae by Regulating the Expression of Type 3 Pili and the Capsule Polysaccharide - Ares, Miguel A.; Fernández-Vázquez, José L.; Rosales-Reyes, Roberto; Jarillo-Quijada, Ma. Dolores; von Bargen, Kristine; Torres, Javier; González-y-Merchand, Jorge A.; Alcántar-Curiel, María D.; De la Cruz, Miguel A. (Frontiers in Cellular and Infection Microbiology, 2016)
Klebsiella pneumoniae is an opportunistic pathogen causing nosocomial infections. Main virulence determinants of K. pneumoniae are pili, capsular polysaccharide, lipopolysaccharide and siderophores. The histone-like nucleoid-structuring protein (H-NS) is a pleiotropic regulator found in several gram-negative pathogens. It has functions both as an architectural component of the nucleoid and as a global regulator of gene expression. We generated a Δhns mutant and evaluated the role of the H-NS nucleoid protein on the virulence features of K. pneumoniae. A Δhns mutant down-regulated the mrkA pilin gene and biofilm formation was affected. In contrast, capsule expression was derepressed in the absence of H-NS conferring a hypermucoviscous phenotype. Moreover, H-NS deficiency affected the K. pneumoniae adherence to epithelial cells such as A549 and HeLa cells. In infection experiments using RAW264.7 and THP-1 differentiated macrophages, the Δhns mutant was less phagocytized than the wild-type strain. This phenotype was likely due to the low adherence to these phagocytic cells. Taken together, our data indicate that H-NS nucleoid protein is a crucial regulator of both T3P and CPS of K. pneumoniae.